Comentarios a la Constitución Española de 1978 / dirigidos por Oscar Alzaga Villaamil. T.VI. Artículos 66 a 80 / Francisco Rubio Llorente...[et al.] - Rubio Llorente, Francisco (1930-2016) Alzaga Villaamil, Óscar
Referencias bibliográficas